Innovations in Project-Based Learning (PBL) Strategies for Elementary School Students - Muhammad Tisna Nugraha; Isyatul Mardiyati (International Journal of Basic Educational Research, 2024)
This research aims to explore the utilization of Project-Based Learning (PBL) in a more innovative manner for implementation in elementary schools. This approach is designed to enhance students' understanding of key PBL concepts and improve their critical thinking skills. The research methodology employed includes literature analysis and case studies from several elementary schools that implement PBL innovatively. Through literature analysis, fundamental PBL concepts are studied and identified. Subsequently, case studies are conducted in several elementary schools that have implemented PBL with innovative approaches. Data are collected through literature review and document analysis. The research findings indicate that innovative PBL, incorporating technology, collaboration, and authentic assessment, can create a more interactive and engaging learning environment for students. However, challenges faced by teachers in implementing this strategy include a lack of resources, curriculum planning, and adequate training. Therefore, recommendations are proposed to provide greater support for teachers, including additional training and better access to supportive technology. Thus, innovation in project-based learning strategies can enhance the effectiveness of student learning in elementary schools.